Foundations of morality in Iran - Atari, Mohammad; Graham, Jesse; Dehghani, Morteza (Evolution and human behavior, 2020)
Most moral psychology research has been conducted in Western, Educated, Industrialized, Rich, and Democratic (WEIRD) societies. As such, moral judgment, as a psychological phenomenon, might be known to researchers only by its WEIRD manifestations. Here, we start with evaluating Moral Foundations Theory (MFT) using the Moral Foundations Questionnaire, and follow up by building a bottom-up model of moral values, in Iran, a non-WEIRD, Muslim-majority, understudied cultural setting. In six studies (N = 1945) we examine the structural validity of the Persian translation of the Moral Foundations Questionnaire, compare moral foundations between Iran and the US, conduct qualitative interviews regarding moral values, expand the nomological network of “Qeirat” as a culture-specific set of moral values, and investigate the pragmatic validity of “Qeirat” in Iranian culture. Our findings suggest an additional moral foundation in Iran, above and beyond the five foundations identified by MFT. Specifically, qualitative studies highlighted the role of “Qeirat” values in Iranian culture, which are comprised of guarding and protectiveness of female kin, romantic partners, broader family, and country. Significant cultural differences in moral values are argued in this work to follow from the psychological systems that, when brought to interact with particular socio-ecological environments, produce different moral structures. This evolutionarily-informed, cross-cultural, mixed-methods research sheds light on moral concerns and their cultural, demographic, and individual-difference correlates in Iran.